Description of Cyclocephala distincta Burmeister (Coleoptera: Scarabaeidae: Dynastinae: Cyclocephalini) immatures and identification key for third instars of some Cyclocephala species - Souza, Thamyrys Bezerra De; Maia, Artur Campos Dália; Albuquerque, Cleide Maria Ribeiro De; Iannuzzi, Luciana (Zootaxa, 2014)
The larval instars and pupa of Cyclocephala distincta Burmeister (Coleoptera: Scarabaeidae: Dynastinae: Cyclocephalini) are described and compared to those of other known congenerics. Adult C. distincta, specialized flower visitors of Neotropical palms (Arecaceae), were collected in an area of native Atlantic Forest cover in the northeastern coast of Brazil and reared in captivity. The larvae of C. distincta diff—er from those of the other congenerics because of a distinctive pattern and arrangement of the setae on the raster.